Photon Radiation Fields Characteristics in Lead for Photon Sources With Energies From 10 to 50 MeV - I. K. Alhagaish; V. K. Sakharov (Глобальная ядерная безопасность, 2022)
According to Monte Carlo calculations of spatial distributions of photon energy in Lead from point isotropic and plane mon-directional monoenergetic sources with energies of 10-50 MeV, define the attenuation coefficient of air Kerma and the dose buildup factors are determined for the studied material. The calculations take into account the contribution of fluorescence, annihilation radiation, and bremsstrahlung radiation. The independence of the Buildup Factors and attenuation coefficient from the angular distribution of the source radiation and the weak dependence of the attenuation coefficient on its energy in the range of 30-50 MeV are shown. Corrections for barrier protection were determined and their independence from the thickness of the shielding material and the photon energy of the source was noted. The obtained information makes it possible to reduce errors in the results of calculations of the thickness for anti-radiation protection of electronic accelerators at high energies, using the developed engineering methods of calculation. The obtained information can also be used in calculations of protection against bremsstrahlung radiation of electronic accelerators by engineering methods.